FRAMEWORK OF POTENTIAL AND CAREER ARCHITECTURE OF BORDER APPARATUS AND ITS RELATIONSHIP WITH SERVICE PERFORMANCE: A SYSTEMATIC LITERATURE REVIEW - Romawi Martin; Maria Christiana Iman Kalis; M. Irfani Hendri (CV. Radja Publika, 2026)
This article aims to develop a systematic quantitative synthesis regarding the framework of potential and career architecture of Indonesian border apparatus and its relationship with service performance. The background of this study is the limited number of studies that directly connect apparatus potential, talent management, career design, and service performance in border areas, even though these regions have geographical, social, security, and service complexities that differ from non-border areas. The method used in this study is a systematic quantitative literature review guided by PRISMA 2020. The literature was selected from the 2016-2026 period through the Scopus, Google Scholar, Garuda, SINTA, DOAJ databases, and open-access journal portals, with priority given to quantitative studies on competence, talent, merit systems, career development, and civil servant performance, as well as contextual studies on Indonesian border governance. A total of 15 research articles were selected for extraction, consisting of 6 core quantitative studies, 3 supporting studies on career architecture and competence, and 6 contextual studies on border areas. The synthesis shows that competence, talent management, merit systems, work discipline, servant leadership, and bureaucratic reform tend to have a positive relationship with apparatus performance. In the border context, this relationship needs to be mediated through a career architecture that integrates potential assessment, talent pools, competency development, rotation, promotion, and placement based on regional needs. This article produces a conceptual model that can be empirically tested through SEM/PLS-SEM on civil servants working in Indonesian border areas.